Uporabnost verižne reakcije s polimerazo v diagnostiki gonoreje - Gubina, Borut (Medicinski razgledi, 2000)
Neisseria gonorrhoeae is a Gram negative diplococcus the cause of sexually transmitted disease gonorrhea. It is transmitted through a promiscuous intercourse, from infected mother to the newborn and from one partner to another. The standard method of diagnostics of gonorrhea is the cultivation and identification of the bacteria, which is based on selective fermentation of different sugars. As the serological diagnostics is not sufficiently reliable, the polymerase chain reaction technique carries important advantages. To asses the use of the polymearase chain reaction COBAS AMPLICOR as a diagnostic method for Neisseria gonorrhoeae infection and its reliabilityin comparison with the classical method. We divided the collected samples in three groups. Group A group of 113 clinical specimen (urine, cervical smear) from the Qutpatient Clinic for Sexually Transmited Diseases, Department of Dermatology in Ljubljana, accounted as a population with high risk of infection; group;B .of 48 medical students (urine rinse of urethra), presumed to be a population with low risk of infection; group C of 31 frozen samples of six different strains from the genus Neisseriaceae that have shown the specificity of the COBAS AMPLICOR polymerase chain reaction test. In the group A we found three gonorrhea positive patients with the polymerase chain reaction method, as well as with the standard method of cultures and fermentation of sugars. All the results of the testing in the group B were negative. In the group C we correctly identified the 10 N. gonorrhoeae among the different Neisseriaceae strains. With our work we proved that COBAS AMPLICOR polymerase chain reaction test is useful for diagnostic and screeningpurposes. It is as reliable as classical diagnostic method and enoughspecific to discern N. gonorrhoeae from other bacteria of the genus of Neisseriaceae.
Keywords: gonoreja; Gonorrhea; spolne bolezni; Diagnosis; bacteria; bakterije; Microbiology; mikrobiologija; Neisseria gonorrhoeae; Isolation and purification; Polymerase chain reaction; diagnostika